PEMBAHASAN INTEGRASI TEKNOLOGI AI DAN BIG DATA DALAM SISTEM INFORMASI MANAJEMEN UNTUK OPTIMALISASI KEPUTUSAN UMKM - Haris Usman; Willy Alija Rahman; Manzis Ilham Maulana; Achmad Illliyyin Abdullah; Muhamad Hariri Fadilah; Ines Heidiani Ikasa (Journal of Research and Publication Innovation, 2025)
Digital The development of digital technology in the era of the Industrial Revolution 4.0 has brought significant changes to business management patterns, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. One of the most significant transformations is the implementation of Artificial Intelligence (AI) and Big Data in Management Information Systems (MIS). The integration of these technologies enables faster, more accurate, and data-driven decision-making processes. This study aims to analyze the role of AI and Big Data in enhancing decision-making efficiency and the competitiveness of MSMEs in Indonesia. The method used is a literature review of five scholarly journals discussing the application of information systems, MSME digitalization, and the influence of technology on business decision-making. The research results indicate that the integration of AI and Big Data can enhance operational efficiency, strengthen marketing strategies, and provide in-depth insights for MSME actors to adapt to market dynamics. However, the adoption of this technology still faces challenges such as low digital literacy, limited capital, and uneven technological infrastructure. This study recommends the need for collaboration between the government, financial institutions, and the private sector to expand access and digital training for MSMEs so that digital transformation can proceed inclusively and sustainably.